INSTRUMENT FOR EVALUATION OF THE ADAPTED ABILITIES FROM THE ELEMENT OF BASKETBALL TECHNIQUE - Goran Šekeljić; Milovan Stamatović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2006)
The idea of the work is clearly defined, precise and objective instrument for evaluation of the adopted abilities from the elements of basketball technique. The intention is to cut into small fragments the chosen elements of technique which are going to be evaluated with numerical value of every piece itself. The model established in that way is possible to compare with motorical forms acquired by those who are been inquired. Every fragment of motorical form has precise numerical value on which basis is possible to quantify by simple numerical total the obtained level of sports- technical education. We consider possible to diminish the influence of subjectivity such as to form schoolmarks more objectivly by precise and high-quality system of evaluation on the basis of clearly cut into small pieces structures of elements of the complete technique. In that case we could talk about real expert evaluation. The results of the research have shown that the method of evaluation conceived in this way has given excellent metrics characteristics and that, statistically verified, has been more objective than the two other methods predicted in the experiment